Multi-scale modeling of triaxial braided composites for FE-based modal analysis of hybrid metal-composite gears. (15th December 2017) - Catera, Piervincenzo Giovanni; Gagliardi, Francesco; Mundo, Domenico; De Napoli, Luigi; Matveeva, Anna; Farkas, Laszlo
Abstract: The paper presents a description of a methodology to accurately estimate the natural frequencies of a hybrid metal-composite gear, where the web is made of a polymer matrix reinforced with two-dimensional (2D) triaxial braided fabrics. The proposed approach is based on a multi-scale composite modeling starting from evaluation of homogenized material properties of the gear web at the meso-scale for a subsequent FE-based modal analysis. For this purpose, the mechanical behavior of a single Repetitive Unit Cell (RUC) at the meso-scale is analyzed with a FE procedure which takes into account the interweaving and cross-section geometry of the yarns, volume fraction and local fiber orientation. It is shown that the described modeling strategy allows to predict gear's natural frequencies that are close to the experimental results. Significant accuracy enhancement is achieved with respect to the model in which the web material is considered as perfectly isotropic.